Perspektif Medis, Sosial, dan Kebijakan dalam Memahami Infertilitas di Indonesia: Sebuah Tinjauan Naratif - Sutanto, Reynardi Larope; Suskhan, Rizki Fauzi; Pratama, Satria Arief; Christian, Christopher; Putra, Elza Nur Warsa; Faruqi, Muhammad; Simanjuntak, Kevin Tadeus; Ali, Najma; Setyawan, Dhanis Adrianto; Suryoadji, Kemal Akbar (Cermin Dunia Kedokteran, 2025)
Introduction: Infertility is a reproductive health problem in various countries, including Indonesia, with a significant impact on population and community productivity. This study aims to assess the urgency of addressing infertility in the context of public health and population control in Indonesia. Methods: This research employs a literature review method, referencing relevant sources. Document searches were conducted through Google Scholar and manual searching using the keywords “(Infertility) AND (Indonesia).” Results: The review found 53 literatures consisting of scientific research, medical consensus, review papers, news, and legal products. Discussion: Infertility is a complex problem that requires a multidisciplinary approach. The discussion is organized into several multidisciplinary sections which include a discussion from the medical side in the form of etiology, risk factors, diagnosis flow, and management of infertility, a review of infertility as a public health problem, the impact of infertility on patients and society, sensitive public communication methods regarding infertility, and recommendations for management and policy regulation regarding infertility for government officials. Conclusion: Addressing infertility in Indonesia requires the support of various parties, including the government, health workers, and the community, to overcome its complex impact.